Desktop Virtualization With N-Computing Technology - Yudhistira Adhitya Pratama (INFOKUM, 2021)
This study discusses how N-Computing works on various operating systems and is tested by direct experimentation with the vSpace application on N-Computing. N-Computing can be used just like a regular PC as a terminal that doesn't require a CPU, hard drive, or CD-ROM. In this practical work research, the author conducted a trial on the performance of the N-Computing X550 series. The author then summarizes the testing process into clearer steps and can know the benefits of N-Computing to users in various aspects. In addition to the operating system, the author also conducted tests on the type and length of the cable so that it can be seen the relationship between N-Computing performance and the cable used. Based on the results of this study, the authors conclude that the N-Computing X550 series is capable of cost savings of more than 40%.